Tit for others' tat: Repeated prisoner's dilemma experiments with third-party monitoring and indirect punishment - Lisa Bruttel; Werner Güth (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2013)
Two pairs of two participants each interact repeatedly in two structurally independent but informationally linked Prisoners Dilemma games. Neither pair receives feedback about past choices by their own partner but is fully informed about the choices by the other pair. Considering this as a four-person infinite horizon game allows for Folk-Theorem-like voluntary cooperation. We ask whether monitoring and indirect punishment with the help of others are comparable to direct monitoring and punishment in establishing and maintaining voluntary cooperation. The treatment effects we find are rather weak. Others monitoring of own activities is only an insufficient substitute for direct observability.
Keywords: C73; C91; D82; D84; 330; experiment; monitoring; prisoner s dilemma